An investigation on presumptive tax non-compliance amongst Zimbabwe SMEs: a case study of Motor trade industry (2011-2014) - Furusa, Pettness (Midlands State University, 2017)
The purpose of this study was to investigate presumptive tax non-compliance among SMEs operators in the Motor Industry. Since the introduction of the presumptive tax in Zimbabwe in 2005, as a means of bringing the informal sector into the tax net, there has been slow progress in achieving compliance especially in the Motor Industry. The existence of the presumptive taxation framework and the accompanying guidelines have been explored and investigated within the Motor trade sector and it was observed that their existence is disseminated and understood within the sector. The study also delved on the adequacy of the personnel in terms of expertise and quantity for the implementation of the guidelines. The existing controls such as e-filing, formalization of the informal sector and the promotion of the cashless economy were also highlighted together with the best practice in the administration of the presumptive taxation framework in the Motor Trade sector. The mixed research design, including the qualitative and quantitative approaches were used for the research. Questionnaires were used to gather the quantitative aspects of the presumptive tax phenomenon, while the interviews provided the qualitative aspects. Tables and charts were used for data presentation and analysis for this study. The findings were that, the presumptive taxation framework exists in Zimbabwe and the implementation guidelines are disseminated to the users and they are understood. The personnel at ZIMRA are adequate for the implementation of the presumptive tax guide implementation and the existing controls are adequate to promote presumptive taxation compliance. It was recommended that, the tax authorities, promote e-filing, simplify the tax administration system and also promote tax amnesty.